Análisis y evaluación de la incidencia de las microburbujas en el tratamiento de agua, a través del desarrollo y estudio de un sistema de operación continua para tratamiento primario de aguas residuales (2020)
This project wants to show the design of a prototype of a continuous flow primary treatment system. Thus, this system is composed in principle by four stages in which the application of the primary treatments involved, such as sedimentation, is evaluated with the design and development of a hydrocyclone, adding the generation of microbubbles, which also involves the own design and elaboration of two prototypes generators, which were designed from a microporous filter for water that generates air bubbles when entering air and that through the use of pressurized water. These bubbles are cut to generate sizes less than 100 microns, with measurements under a microscope thanks to the image analysis in Matlab, allowing the design of a low-cost system, In addition to this, it must be said that its help is shown for the primary treatment of waters contaminated with certain materials, where it also shows signs of accumulation, agglomeration and separation of suspended and dissolved solids, the results are evaluated according to turbidity and coloration of the resulting water with respect to its previous stages.